Isolating membrane, battery and electric device

By using an isolation film with a dendritic structure in the battery, the problem that the battery is prone to internal short circuit and thermal runaway under high temperature conditions is solved, and the effect of improving the battery's heat resistance and circulation performance is achieved.

CN119833886AActive Publication Date: 2025-04-15CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202311628161.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-04-15
Estimated Expiration
2043-11-29

AI Technical Summary

Technical Problem

Existing batteries are prone to internal short circuits and thermal runaway under high temperature conditions, leading to safety accidents, and it is difficult to balance energy density and service life.

Method used

An isolation film is used, which includes a porous substrate and a coating, the coating consists of a fiber material and a granular filler, the fiber material consists of a first fiber material and a second fiber material, the average length of the first fiber material is greater than 800 nm, and the average length ratio of the first fiber material to the second fiber material is greater than or equal to 2.4.

Benefits of technology

Through the combination of fiber materials and structural design, a dendritic coating is formed, which reduces the content of free filler particles, improves the heat resistance of the isolation film and the electrolyte wetting property, extends the cycle life of the battery and improves its reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833886A_ABST
    Figure CN119833886A_ABST
Patent Text Reader

Abstract

The invention discloses an isolating membrane, a battery and a power utilization device, the isolating membrane comprises a porous base material and a coating arranged on at least one surface of the porous base material, the coating comprises fiber materials and granular filler, the fiber materials comprise a first fiber material and a second fiber material, the average length of the first fiber material is recorded as L1, and the average length of the second fiber material is recorded as L2; the average length of the second fiber material is recorded as L2, L1 is greater than 800nm, and L1 / L2 is greater than or equal to 2.4. According to the invention, the battery has high reliability and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an isolation film, a battery and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. With the application and promotion of batteries, their reliability, especially thermal stability, has received more and more attention. However, the current methods for improving the thermal stability of batteries are often not conducive to balancing the energy density and service life of the battery; in addition, when the battery temperature continues to rise, it is easy to cause internal short circuits and induce thermal runaway of the battery, and even cause safety accidents such as fire and explosion of the battery. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention

[0003] The present application provides a separation film, a battery and an electrical device, which can enable the battery to have high reliability and good cycle performance.

[0004] In a first aspect, the present application provides an isolation membrane, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, the coating comprising a fiber material and a granular filler, the fiber material comprising a first fiber material and a second fiber material, the average length of the first fiber material being denoted as L1, the average length of the second fiber material being denoted as L2, L1 being greater than 800 nm, and L1 / L2 ≥ 2.4.

[0005] By making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, since the second fiber material has a smaller average length, it can be flexibly inserted between the first fiber materials to play a connecting role, so that the coating can be integrated and the coating has a dendritic structure, thereby reducing the content of free filler particles in the coating, reducing the pore clogging problem, and improving the heat resistance of the isolation membrane.

[0006] In addition, by making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, during liquid injection, the electrolyte can also quickly wet the isolation membrane along the first fiber material and the second fiber material. As a result, the isolation membrane can also have good electrolyte wettability and liquid retention during rapid charge and discharge of the battery, which is beneficial to ion transport and reducing dendrites, thereby enabling the battery to have good cycle performance.

[0007] Therefore, by making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, the coating can have a dendritic structure, and the first fiber material, the second fiber material and the filler particles can be overlapped to form an integrated coating. Therefore, the isolation membrane provided in the embodiment of the present application can have good heat resistance, good air permeability, and good electrolyte wettability and liquid retention, which is conducive to reducing the risk of failure during battery use, and can also make the battery have high reliability and good cycle performance.

[0008] In some embodiments, L1 / L2 is 2.4-9.0, optionally 2.7-5.8.

[0009] By further adjusting L1 / L2 within the above range, the first fiber material and the second fiber material can be better overlapped, which is beneficial to further increase the heat resistance of the isolation membrane, reduce the content of free filler particles in the coating, and facilitate the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane, thereby making the battery have higher reliability and better cycle performance.

[0010] In some embodiments, the average length L1 of the first fiber material is 850 nm-3000 nm, and optionally 1000 nm-2000 nm.

[0011] In some embodiments, the average length L2 of the second fiber material is 200 nm-800 nm, and optionally 300 nm-550 nm.

[0012] By further adjusting the average length of the first fiber material and / or the second fiber material within the above range, it is beneficial to further reduce the risk of failure during the use of the battery and further improve the cycle performance of the battery.

[0013] In some embodiments, the first fiber material has an average diameter greater than an average diameter of the second fiber material.

[0014] By further making the average diameter of the first fiber material larger than the average diameter of the second fiber material, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby further improving the heat resistance of the isolation membrane, reducing the pore blocking problem of the isolation membrane, and improving the electrolyte wettability and liquid retention of the isolation membrane, which in turn helps to further reduce the risk of failure during battery use and further improve the cycle performance of the battery.

[0015] In some embodiments, the average diameter of the first fiber material is less than or equal to 100 nm, and may be 25 nm-75 nm.

[0016] In some embodiments, the average diameter of the second fiber material is 12 nm-40 nm, and optionally 15 nm-32 nm.

[0017] By adjusting the average diameter of the first fiber material and / or the second fiber material within the above range, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby helping to improve the heat resistance of the isolation membrane, reduce the pore blocking problem of the isolation membrane, and enhance the electrolyte wettability and liquid retention of the isolation membrane, thereby further reducing the risk of failure during battery use and further improving the cycle performance of the battery.

[0018] In some embodiments, the aspect ratio of the first fiber material is greater than the aspect ratio of the second fiber material.

[0019] By further making the aspect ratio of the first fiber material greater than that of the second fiber material, it is beneficial for the first fiber material to connect more filler particles, and for the second fiber material to better connect between the first fiber material so that the first fiber material and the second fiber material overlap to form a dendritic structure. It is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, reducing the content of free filler particles, thereby improving the heat resistance of the separator, reducing the problem of pore blocking of the separator, and improving the electrolyte wettability and liquid retention of the separator. Therefore, by further making the aspect ratio of the first fiber material greater than that of the second fiber material, the risk of failure during battery use can be further reduced, and the cycle performance of the battery can be further improved.

[0020] In some embodiments, the aspect ratio of the first fiber material is 12-100, and can be 20-50.

[0021] In some embodiments, the aspect ratio of the second fiber material is 10-70, and can be 15-40.

[0022] By adjusting the aspect ratio of the first fiber material and / or the second fiber material within the above range, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby helping to improve the heat resistance of the isolation membrane, reduce the pore blocking problem of the isolation membrane, and enhance the electrolyte wettability and liquid retention of the isolation membrane, thereby further reducing the risk of failure during battery use and further improving the cycle performance of the battery.

[0023] In some embodiments, the content of the first fiber material is less than the content of the second fiber material.

[0024] By adjusting the content of the first fiber material to be less than that of the second fiber material, more second fiber materials can be better connected between the first fiber materials, which is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure with more branches, thereby facilitating the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane, and further improving the battery cycle performance.

[0025] In some embodiments, the content of the first fiber material is denoted as W 11 , the content of the second fiber material is recorded as W 12 , are based on the total mass of the coating, W 11 / W 12 It is 0.20-0.95, and can be optionally 0.40-0.75.

[0026] By further adjusting W 11 / W 12 Within the above range, the performance of the separator and the battery can be further improved.

[0027] In some embodiments, the content of the first fiber material is denoted as W 11 , based on the total mass of the coating, W 11 5wt%-13wt%.

[0028] In some embodiments, the content of the second fiber material is denoted as W 12 , based on the total mass of the coating, W 12 9wt%-21wt%.

[0029] By adjusting the content of the first fiber material and / or the second fiber material within the above range, the first fiber material and the second fiber material can be better overlapped, which is beneficial to increase the heat resistance of the isolation membrane, reduce the content of free filler particles in the coating, and facilitate the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane.

[0030] In some embodiments, the first fiber material and the second fiber material each independently include at least one of an organic fiber material and an inorganic fiber material.

[0031] Optionally, the organic fiber material includes at least one of nanocellulose, polytetrafluoroethylene nanofibers and polyamide nanofibers.

[0032] Optionally, the inorganic fiber material includes at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide and glass fiber.

[0033] In some embodiments, the first fiber material and the second fiber material each independently comprise nanocellulose.

[0034] Optionally, the nanocellulose includes a modified group, and the modified group includes at least one of an amine group, a carboxyl group, an aldehyde group, a sulfonic acid group and a phosphoric acid group, and more optionally includes at least one of a sulfonic acid group and a phosphoric acid group.

[0035] Optionally, the nanocellulose includes hydroxyl groups and modified groups, and the molar ratio of the modified groups to the hydroxyl groups is 1:4 to 4:1, and more preferably 2:3 to 7:3.

[0036] In some embodiments, the granular filler includes a first filler and a second filler, and the average particle size D1 of the first filler is smaller than the average particle size D2 of the second filler.

[0037] By making the granular filler include the first filler and the second filler at the same time, and making the average particle size D1 of the first filler smaller than the average particle size D2 of the second filler, a certain space can be formed around the second filler particles in the coating, thereby improving the air permeability of the isolation membrane and facilitating the preservation of the electrolyte after infiltration, thereby facilitating the improvement of the electrolyte retention and ion transmission properties of the isolation membrane; the first filler particles can also be filled in the gaps between the second filler particles, thereby reducing the thermal shrinkage of the isolation membrane and improving the heat resistance of the isolation membrane.

[0038] In some embodiments, the average particle size D1 of the first filler and the average particle size D2 of the second filler satisfy D2 / D1≥1.2; optionally, D2 / D1 is 1.5-16, and more optionally 2-8.

[0039] By further adjusting D2 / D1 within the above range, the performance of the isolation membrane can be better improved so that it has good air permeability, good electrolyte wettability and liquid retention as well as good heat resistance. The first filler and the second filler can also be better overlapped with the first fiber material and the second fiber material to form an integrated coating, thereby reducing the content of free filler particles, thereby further reducing the risk of failure during battery use and further improving the battery's cycle performance.

[0040] In some embodiments, the first filler has a secondary particle morphology and the second filler has a primary particle morphology.

[0041] The secondary particles are formed by agglomeration of multiple primary particles, and the first filler in the secondary particle morphology can better overlap with the first fiber material and the second fiber material to form an integrated coating, thereby helping to make the coating have a stable spatial network structure and helping to improve the heat resistance of the separator. The second filler in the primary particle morphology is conducive to reducing the moisture content of the coating, improving the air permeability and ion conductivity of the coating, and thus helping to improve the cycle performance of the battery.

[0042] In some embodiments, a ratio L1 / D2 of an average length L1 of the first fiber material to an average particle size D2 of the second filler is 3.0-5.0.

[0043] By making L1 / D2 within the above range, the first fiber material in the coating can be connected to more second filler particles, which is beneficial to form an integrated coating, and further beneficial to improving the heat resistance, electrolyte wettability and liquid retention of the isolation membrane.

[0044] In some embodiments, a ratio L2 / D1 of an average length L2 of the second fiber material to an average particle size D1 of the first filler is 2.0-4.0.

[0045] By making L2 / D1 within the above range, the second fiber material in the coating can be connected to more second filler particles, which is beneficial to form an integrated coating, and further beneficial to improving the heat resistance, electrolyte wettability and liquid retention of the isolation membrane.

[0046] In some embodiments, the average particle size D1 of the first filler is less than 200 nm, and may be 50 nm-185 nm.

[0047] When the average particle size of the first filler is within the above range, it is easier to overlap with the first fiber material and the second fiber material to form an integrated coating, thereby improving the heat resistance, electrolyte wettability and liquid retention of the isolation membrane.

[0048] In some embodiments, the average particle size D2 of the second filler is 200 nm-800 nm, and can be optionally 210 nm-400 nm.

[0049] The average particle size of the second filler is within the above range, which is beneficial for maintaining a stable pore structure of the coating during long-term charge and discharge, reducing the moisture content of the coating, and improving the air permeability and ion conductivity of the coating, thereby improving the cycle performance of the battery.

[0050] In some embodiments, the average particle size of the primary particles constituting the first filler is 10 nm-50 nm, and can be 15 nm-35 nm.

[0051] The average particle size of the primary particles constituting the first filler is within the above range, so that the first filler has a good secondary particle morphology, which is beneficial to improving the overlapping effect of the first filler with the first fiber material and the second fiber material.

[0052] In some embodiments, the specific surface area of ​​the first filler is greater than the specific surface area of ​​the second filler.

[0053] The first filler has a larger specific surface area and better affinity with the first fiber material and the second fiber material, so that the coating can have a more stable spatial network structure and the isolation membrane has better heat resistance and higher ion conductivity; the second filler has a smaller specific surface area, which is beneficial to reducing the moisture content of the isolation membrane.

[0054] In some embodiments, the specific surface area of ​​the first filler is greater than or equal to 20 m 2 / g, optional 30m 2 / g-80m 2 / g.

[0055] When the specific surface area of ​​the first filler is within the above range, it is beneficial to further improve the heat resistance and ion conductivity of the isolation membrane; in addition, it is also beneficial to improve the affinity of the first filler with the first fiber material and the second fiber material, so that the coating can have a more stable spatial network structure, and the isolation membrane has better heat resistance and higher ion conductivity.

[0056] In some embodiments, the specific surface area of ​​the second filler is less than 20 m 2 / g, optional 5m 2 / g-15m 2 / g.

[0057] The specific surface area of ​​the second filler is within the above range, which is beneficial to reducing the moisture content of the isolation membrane, thereby reducing the battery capacity decay rate and improving the cycle performance of the battery.

[0058] In some embodiments, the content of the first filler is greater than the content of the second filler.

[0059] This is conducive to better exerting the functions of the first filler and the second filler, improving the heat resistance of the isolation membrane, and improving the electrolyte retention of the isolation membrane.

[0060] In some embodiments, the content of the first filler is denoted as W 21 , the content of the second filler is recorded as W 22 , are based on the total mass of the coating, W 22 / W 21 It is 0.10-0.80, and can be selected as 0.25-0.50.

[0061] In some embodiments, the content of the first filler is denoted as W 21 , based on the total mass of the coating, W 21 It is 20wt%-70wt%, and can be optionally 36wt%-61.5wt%.

[0062] The content of the first filler within the above range is conducive to the coating slurry having a suitable viscosity, which is more conducive to coating; in addition, it is also conducive to the coating having a more stable spatial network structure, thereby making the isolation membrane have better heat resistance and higher ion conductivity.

[0063] In some embodiments, the content of the second filler is denoted as W 22 , based on the total mass of the coating, W 22 It is 5wt%-60wt%, and can be optionally 10wt%-35wt%.

[0064] The content of the second filler within the above range is beneficial for the coating to maintain a stable pore structure during long-term charge and discharge, thereby reducing the moisture content of the isolation membrane and preserving the electrolyte after infiltration, thereby improving the cycle performance of the battery.

[0065] In some embodiments, the first filler includes at least one of inorganic particles and organic particles.

[0066] Optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silica, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate and magnesium fluoride. More optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, silica, titanium oxide, zinc oxide, cerium oxide and barium titanate.

[0067] Optionally, the organic particles include at least one of polystyrene and polyacrylic acid wax.

[0068] In some embodiments, the second filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.

[0069] In some embodiments, the first filler includes inorganic particles with secondary particle morphology, and the crystal form of the inorganic particles with secondary particle morphology includes at least two of α-crystal form, θ-crystal form, γ-crystal form and η-crystal form. Optionally, the crystal form of the inorganic particles with secondary particle morphology includes at least two of α-crystal form, θ-crystal form and γ-crystal form.

[0070] Optionally, the content of the inorganic particles with α-crystal secondary particle morphology in the inorganic particles with secondary particle morphology is greater than or equal to 1.2 wt%, and more optionally 1.2 wt% to 10 wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0071] Optionally, the content of inorganic particles with secondary particle morphology of θ crystal type in the inorganic particles with secondary particle morphology is greater than or equal to 50wt%, and more optionally 60wt% to 85wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0072] Optionally, the content of inorganic particles with secondary particle morphology of γ crystal type in the inorganic particles with secondary particle morphology is greater than or equal to 10wt%, and more optionally 15wt% to 60wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0073] Optionally, the content of inorganic particles with η crystal secondary particle morphology in the inorganic particles with secondary particle morphology is less than or equal to 5wt%, and more optionally less than or equal to 2wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0074] In some embodiments, the second filler includes inorganic particles in a primary particle morphology, and the crystal form of the inorganic particles in the primary particle morphology includes at least one of an α crystal form and a γ crystal form, and may optionally include an α crystal form.

[0075] Optionally, the content of inorganic particles with α-crystal primary particle morphology in the second filler is greater than or equal to 90 wt %, and more optionally 95 wt % to 100 wt %, based on the total mass of the second filler.

[0076] In some embodiments, the coating further comprises a non-particulate binder.

[0077] Optionally, the non-granular binder comprises an aqueous solution binder.

[0078] Optionally, the content of the non-granular binder in the coating is less than or equal to 2 wt %, based on the total mass of the coating.

[0079] In some embodiments, the isolation film further includes an adhesive layer, and the adhesive layer is disposed on at least a portion of the surface of the coating layer.

[0080] Optionally, the adhesive layer includes a granular adhesive. More preferably, the granular adhesive includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.

[0081] In some embodiments, the thickness of the porous substrate is less than or equal to 5 μm, and may be 3 μm-4.5 μm.

[0082] In some embodiments, the thickness of the coating is less than or equal to 3 μm, and can be optionally 0.3 μm-2 μm.

[0083] In some embodiments, the thermal shrinkage rates of the isolation film in the transverse direction and in the longitudinal direction at 150° C. for 1 hour are both less than 2%.

[0084] In some embodiments, the air permeability of the isolation membrane is less than or equal to 300s / 100mL, and can be optionally 100s / 100mL-240s / 100mL.

[0085] In some embodiments, the wetting speed of the isolation film is greater than or equal to 3 mm / s, and can be optionally 5 mm / s-15 mm / s.

[0086] In a second aspect, the present application provides a battery, comprising the isolation membrane of the first aspect of the present application.

[0087] In a third aspect, the present application provides an electrical device comprising the battery of the second aspect of the present application.

[0088] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0089] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0090] Figure 1 A schematic diagram showing a battery cell provided by some embodiments of the present application.

[0091] Figure 2A schematic diagram of an exploded view of a battery cell provided by some embodiments of the present application is shown.

[0092] Figure 3 A schematic diagram of a battery module provided in some embodiments of the present application is shown.

[0093] Figure 4 A schematic diagram of a battery pack provided in some embodiments of the present application is shown.

[0094] Figure 5 yes Figure 4 An exploded diagram of the battery pack is shown.

[0095] Figure 6 A schematic diagram of an electrical device provided in some embodiments of the present application is shown.

[0096] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0097] Hereinafter, the embodiments of the separator, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0098] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0099] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0100] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0101] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0102] If not otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0103] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0104] In the description of the embodiments of the present application, unless otherwise specified, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, a first feature being “above”, “above”, or “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, or “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0105] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0106] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0107] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0108] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0109] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0110] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0111] A battery cell generally includes an electrode assembly and an electrolyte. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0112] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0113] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.

[0114] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0115] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0116] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0117] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0118] The battery provided in the embodiments of the present application may include but is not limited to a lithium battery, a sodium battery, such as a lithium ion battery, a sodium ion battery, and the like.

[0119] Typically, an electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and its main function is to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass freely to form a loop.

[0120] The isolation membranes currently used in commercial batteries are usually polyolefin porous membranes, which have poor heat resistance. When heated, they will produce a significant thermal shrinkage effect, causing the positive and negative electrodes inside the battery to come into direct contact, resulting in an internal short circuit, which can easily induce thermal runaway. In severe cases, the battery may also cause safety accidents such as fire and explosion.

[0121] In order to solve the above problems, the current measures mainly involve coating a heat-resistant inorganic ceramic layer on the polyolefin porous membrane, which can increase the mechanical strength of the separator, reduce the shrinkage of the separator when heated, and reduce the risk of short circuit between the positive and negative electrodes inside the battery. However, the particle size of commercially available inorganic ceramic particles is relatively large, which will increase the overall thickness of the separator, resulting in an inability to balance the energy density of the battery, especially in the field of power batteries, which is not conducive to improving the range.

[0122] An embodiment of the present application provides an isolation film.

[0123] The isolation membrane includes a porous substrate and a coating disposed on at least one surface of the porous substrate. The coating includes a fiber material and a granular filler, the fiber material includes a first fiber material and a second fiber material, the average length of the first fiber material is recorded as L1, the average length of the second fiber material is recorded as L2, L1 is greater than 800nm, and L1 / L2≥2.4.

[0124] The term "fibrous material" refers to a material having an aspect ratio of 5 or more.

[0125] The first fiber material and the second fiber material have a linear structure, and the average length L1 of the first fiber material is greater than 800nm. It has a larger average length, so that more filler particles can be connected, but the overlap effect between the first fiber materials is usually poor, and the first fiber material is more likely to contact with larger filler particles, which may cause some smaller filler particles to be in a free state, which is prone to pore blocking problems and also easily reduces the heat resistance of the isolation membrane. By making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, since the second fiber material has a smaller average length, it can be flexibly inserted between the first fiber materials to play a connecting role, so that the coating can be integrated and the coating has a dendritic structure, which can reduce the content of free filler particles in the coating, reduce pore blocking problems, and improve the heat resistance of the isolation membrane. And compared with inorganic ceramic coatings, the coating of the isolation membrane provided in the embodiment of the present application can take into account both low thickness and high heat resistance.

[0126] In addition, by making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, during liquid injection, the electrolyte can also quickly wet the isolation membrane along the first fiber material and the second fiber material. As a result, the isolation membrane can also have good electrolyte wettability and liquid retention during rapid charge and discharge of the battery, which is beneficial to ion transport and reducing dendrites, thereby enabling the battery to have good cycle performance.

[0127] Therefore, by making the fiber material include the first fiber material and the second fiber material at the same time, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800nm ​​and L1 / L2≥2.4, the coating can have a dendritic structure, and the first fiber material, the second fiber material and the filler particles can be overlapped to form an integrated coating. Therefore, the isolation membrane provided in the embodiment of the present application can have good heat resistance, good air permeability, and good electrolyte wettability and liquid retention, which is conducive to reducing the risk of failure during battery use, and can also make the battery have high reliability and good cycle performance.

[0128] In addition, the isolation membrane provided in the embodiment of the present application has good heat resistance, so that the isolation membrane can have high heat resistance while being relatively thin, which is also beneficial for the battery to have a high energy density; at the same time, the isolation membrane provided in the embodiment of the present application can also reduce the probability of misalignment and short circuit between the edges of the positive and negative electrodes during the battery preparation process, thereby reducing the risk of failure during the use of the battery while reducing the risk of failure during the battery preparation process, thereby improving the process quality rate of the battery product.

[0129] In some embodiments, the average length L1 of the first fiber material and the average length L2 of the second fiber material can satisfy L1 / L2 of 2.4-9.0, for example, 2.4, 2.7, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8, 6.0, 6.3, 6.6, 6.9, 7.2, 7.5, 7.8, 8.2, 8.6, 9.0, or a range consisting of any of the above values.

[0130] Optionally, L1 / L2 can be 2.7-5.8, 3.0-5.0.

[0131] By further adjusting L1 / L2 within the above range, the first fiber material and the second fiber material can be better overlapped, which is beneficial to further increase the heat resistance of the isolation membrane, reduce the content of free filler particles in the coating, and facilitate the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane, thereby making the battery have higher reliability and better cycle performance.

[0132] In some embodiments, the average length L1 of the first fiber material may be 850 nm-3000 nm, and optionally 1000 nm-2000 nm.

[0133] By adjusting the average length of the first fiber material within the above range, more filler particles can be connected to the first fiber material of the same mass.

[0134] In some embodiments, the average length L2 of the second fiber material may be 200 nm-800 nm, optionally 300 nm-550 nm.

[0135] By adjusting the average length of the second fiber material within the above range, the second fiber material can be better connected to the first fiber material.

[0136] By adjusting the average length of the first fiber material and / or the second fiber material within the above range, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, reducing the content of free filler particles, thereby improving the heat resistance of the isolation membrane and reducing the pore blocking problem of the isolation membrane. By adjusting the average length of the first fiber material and / or the second fiber material within the above range, it is also beneficial for the electrolyte to quickly wet the isolation membrane along the first fiber material and the second fiber material, improving the electrolyte wettability and liquid retention of the isolation membrane, thereby facilitating ion transmission and reducing dendrites. By adjusting the average length of the first fiber material and / or the second fiber material within the above range, it is also beneficial for the coating slurry to have a suitable viscosity, which is beneficial for coating and improving the uniformity and consistency of the coating.

[0137] Therefore, by further adjusting the average length of the first fiber material and / or the second fiber material within the above range, it is beneficial to further reduce the risk of failure during the use of the battery and to further improve the cycle performance of the battery.

[0138] In some embodiments, the average diameter of the first fiber material can be greater than the average diameter of the second fiber material.

[0139] When the average length of the second fiber material is small and the average diameter is large, the connecting effect of the second fiber material between the first fiber materials of the same mass will be poor, which is not conducive to overlapping with the first fiber material to form a dendritic structure.

[0140] By further making the average diameter of the first fiber material larger than the average diameter of the second fiber material, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby further improving the heat resistance of the isolation membrane, reducing the pore blocking problem of the isolation membrane, and improving the electrolyte wettability and liquid retention of the isolation membrane, which in turn helps to further reduce the risk of failure during battery use and further improve the cycle performance of the battery.

[0141] In some embodiments, the average diameter of the first fiber material may be less than or equal to 100 nm, and may be 25 nm to 75 nm.

[0142] In some embodiments, the average diameter of the second fiber material may be 12 nm to 40 nm, and optionally 15 nm to 32 nm.

[0143] By adjusting the average diameter of the first fiber material and / or the second fiber material within the above range, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby helping to improve the heat resistance of the isolation membrane, reduce the pore blocking problem of the isolation membrane, and enhance the electrolyte wettability and liquid retention of the isolation membrane, thereby further reducing the risk of failure during battery use and further improving the cycle performance of the battery.

[0144] In some embodiments, the aspect ratio of the first fiber material may be greater than the aspect ratio of the second fiber material.

[0145] By further making the aspect ratio of the first fiber material greater than that of the second fiber material, it is beneficial for the first fiber material to connect more filler particles, and for the second fiber material to better connect between the first fiber material so that the first fiber material and the second fiber material overlap to form a dendritic structure. It is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, reducing the content of free filler particles, thereby improving the heat resistance of the separator, reducing the problem of pore blocking of the separator, and improving the electrolyte wettability and liquid retention of the separator. Therefore, by further making the aspect ratio of the first fiber material greater than that of the second fiber material, the risk of failure during battery use can be further reduced, and the cycle performance of the battery can be further improved.

[0146] In some embodiments, the aspect ratio of the first fiber material may be 12-100, and optionally 20-50.

[0147] In some embodiments, the aspect ratio of the second fiber material may be 10-70, and optionally 15-40.

[0148] By adjusting the aspect ratio of the first fiber material and / or the second fiber material within the above range, it is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure, and it is also beneficial for the first fiber material, the second fiber material and the filler particles to overlap to form an integrated coating, thereby reducing the content of free filler particles, thereby helping to improve the heat resistance of the isolation membrane, reduce the pore blocking problem of the isolation membrane, and enhance the electrolyte wettability and liquid retention of the isolation membrane, thereby further reducing the risk of failure during battery use and further improving the cycle performance of the battery.

[0149] The average length and average diameter of the first fiber material and the second fiber material can be measured by the following method: a sample of 3.6 mm×3.6 mm is cut out from any area of ​​the isolation film, and the microscopic morphology of the coating in the sample is measured by a scanning electron microscope (such as ZEISS Sigma 300), and a high vacuum mode is selected, the working voltage is 3 kV, and the magnification is 30,000 times to obtain a SEM image; according to the obtained SEM image, multiple (for example, more than 5) test areas are selected for length statistics, and the size of each test area is 0.5 μm×0.5 μm, and then the average length of the first fiber material obtained in each test area is taken as the average length of the first fiber material, and the average length of the second fiber material obtained in each test area is taken as the average length of the second fiber material; according to the obtained SEM image, a Nano microscope is used to measure the average length of the first fiber material and the average diameter of the second fiber material. Measurer particle size distribution statistical software selects multiple (for example, more than 5) test areas for diameter statistics, where the size of each test area is 0.5μm×0.5μm, and then takes the average value of the diameters of the first fiber material obtained in each test area as the average diameter of the first fiber material, and takes the average value of the diameters of the second fiber material obtained in each test area as the average diameter of the second fiber material.

[0150] In some embodiments, the first fiber material and the second fiber material may each independently include at least one of an organic fiber material and an inorganic fiber material.

[0151] Alternatively, the organic fiber material may include at least one of nanocellulose, polytetrafluoroethylene nanofibers, and polyamide nanofibers.

[0152] Alternatively, the inorganic fiber material may include at least one of halloysite nanotubes, nanorod-shaped alumina, nanorod-shaped boehmite, nanorod-shaped silica, and glass fibers.

[0153] In some embodiments, the first fiber material and the second fiber material may each independently comprise nanocellulose.

[0154] Nanocellulose is a general term for cellulose with any dimension at the nanometer level (e.g., within 100 nm). It has both the properties of cellulose and the properties of nanoparticles. Nanocellulose can be a polymer nanomaterial extracted from wood, cotton, etc. in nature by one or more means of chemistry, physics, biology, etc. It has the advantages of wide sources, low cost, biodegradability, high modulus, and high specific surface area. Therefore, it is an excellent substitute for traditional petrochemical resources and can effectively alleviate environmental pollution and petrochemical resource shortages.

[0155] Nanocellulose has good high temperature resistance and its volume changes little after being heated, thus improving the heat resistance of the separator. Nanocellulose has a low density, thus reducing the mass of the battery and improving the mass energy density of the battery. Nanocellulose itself contains a large number of hydroxyl groups, which can be connected to filler particles, porous substrates, etc. through hydrogen bonds, van der Waals forces, etc., thus enhancing the adhesion between coatings and between coatings and porous substrates, and reducing the problem of powder loss. In addition, the structure after nanocellulose and filler particles are overlapped can have tiny nanopores, thus reducing current leakage, and also allowing the separator to have good electrolyte wettability and liquid retention, as well as good voltage breakdown resistance.

[0156] Optionally, the nanocellulose includes a modification group, which may include at least one of an amine group, a carboxyl group, an aldehyde group, a sulfonic acid group, and a phosphoric acid group, and more optionally includes at least one of a sulfonic acid group and a phosphoric acid group.

[0157] When nanocellulose has the above-mentioned specific modified groups, on the one hand, it can effectively improve the heat resistance of the isolation membrane, enhance the thermal stability of the battery, and reduce the risk of failure during battery use; on the other hand, it can also improve the bonding strength between the coating and the porous substrate.

[0158] When nanocellulose has the above-mentioned specific modified groups, it is also beneficial to overlap with filler particles to form an integrated coating, thereby enabling the coating to have a stable spatial network structure, thereby improving the electrolyte wettability and liquid retention of the separator, improving the ion transmission characteristics and voltage breakdown resistance of the separator; it is also beneficial to match high-voltage positive electrode active materials and further improve the energy density of the battery. In addition, the presence of modified groups can also reduce the proportion of hydroxyl groups, thereby facilitating the coating slurry to have a suitable viscosity and more conducive to coating, thereby improving the production efficiency of the separator and improving the uniformity and consistency of the coating.

[0159] Optionally, the nanocellulose includes hydroxyl groups and modified groups, and the molar ratio of the modified groups to the hydroxyl groups may be 1:4 to 4:1, more preferably 2:3 to 7:3.

[0160] When the molar ratio of the modified group to the hydroxyl group is within the above range, the heat resistance, ion transport properties, electrolyte wettability and liquid retention of the isolation membrane can be further improved, which is beneficial to reduce the risk of failure during battery use and improve the cycle performance of the battery.

[0161] The type of modified groups in nanocellulose can be determined by infrared spectroscopy. For example, the infrared spectrum of the material can be tested to determine the characteristic peaks contained therein, thereby determining the type of modified groups. Specifically, the material can be analyzed by infrared spectroscopy using instruments and methods known in the art, for example, using an infrared spectrometer (such as the IS10 Fourier transform infrared spectrometer of Nicolet Corporation, USA), and tested according to the general rules for infrared spectroscopy analysis methods of GB / T 6040-2019.

[0162] The molar ratio of modified groups to surface hydroxyl groups in nanocellulose can be measured by the following method: the hydroxyl values ​​(milligrams of potassium hydroxide equivalent to the hydroxyl content in each gram of sample) of raw cellulose and nanocellulose are measured according to the phthalic anhydride method in GB / T12008.3-2009, and the numerical unit obtained is mg KOH / g, which is converted into mmol / g as the hydroxyl content. The content of modified groups (i.e., the content of modified hydroxyl groups) can be obtained by subtracting the hydroxyl content of nanocellulose from the hydroxyl content of raw cellulose, and the molar ratio of modified groups to surface hydroxyl groups can be calculated.

[0163] In some embodiments, nanocellulose can be obtained by the following method: providing cellulose powder with a whiteness greater than or equal to 80%; mixing and reacting the obtained cellulose powder with a modified solution, washing and removing impurities, adjusting the pH to neutral, and grinding and cutting to obtain nanocellulose.

[0164] Optionally, the cellulose powder with a whiteness greater than or equal to 80% can be purchased from the market, or obtained by chemical methods (such as acid hydrolysis, alkali treatment, Tempo catalytic oxidation), biological methods (such as enzyme treatment), mechanical methods (such as ultrafine grinding, ultrasonic crushing, high-pressure homogenization), etc. The fiber raw material used to prepare the cellulose powder with a whiteness greater than or equal to 80% can include plant fibers, such as cotton fibers (such as cotton fibers, kapok fibers), hemp fibers (such as sisal fibers, ramie fibers, jute fibers, flax fibers, hemp fibers, abaca fibers, etc.), palm fibers, wood fibers, bamboo fibers, and grass fibers.

[0165] In some embodiments, the cellulose powder with a whiteness greater than or equal to 80% can also be prepared by the following method: after the fiber raw material is loosened and deslagging, it is cooked with an alkali solution (for example, an aqueous NaOH solution, whose concentration can be 4wt% to 20wt%, optionally 5wt% to 15wt%), and then sequentially washed with water to remove impurities (for example, the number of washings is 3 to 6 times), bleached (for example, sodium hypochlorite and / or hydrogen peroxide can be used), acid washed to remove impurities, washed with water to remove impurities, water driven, and air dried to obtain cellulose powder.

[0166] In some embodiments, the modified solution may be an acid solution (eg, aqueous sulfuric acid solution, aqueous phosphoric acid solution, aqueous acetic acid solution) or an alkaline solution (eg, urea organic solvent solution). Optionally, the modified solution is an acid solution.

[0167] Optionally, the concentration of the acid solution may be 5wt% to 80wt%. When the modified solution is a sulfuric acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining a cellulose powder having a sulfonic acid group. When the modified solution is a phosphoric acid aqueous solution, the concentration of the acid solution may be 45wt% to 75wt%, thereby obtaining a cellulose powder having a phosphoric acid group. When the modified solution is an acetic acid aqueous solution, the concentration of the acid solution may be 40wt% to 80wt%, thereby obtaining a cellulose powder having a carboxylic acid group.

[0168] Alternatively, the urea organic solvent solution may be a urea xylene solution, thereby obtaining cellulose powder having amine groups.

[0169] In some embodiments, optionally, the mass ratio of cellulose powder to modifying solution may be 1:2.5 to 1:50, optionally 1:5 to 1:30.

[0170] When the modified solution is a sulfuric acid aqueous solution, the mass ratio of cellulose powder to the acid solution can be 1:5 to 1:30. When the modified solution is a phosphoric acid aqueous solution, the mass ratio of cellulose powder to the acid solution can be 1:5 to 1:30. When the modified solution is an acetic acid aqueous solution, the mass ratio of cellulose powder to the acid solution can be 1:5 to 1:30. When the modified solution is a urea organic solvent solution, the mass ratio of cellulose powder to the urea organic solvent solution can be 1:4 to 1:40.

[0171] In some embodiments, when the modified solution is an acid solution, the reaction can be carried out at a temperature not higher than 80°C, optionally at 30°C to 60°C, and the reaction time of the cellulose powder and the modified solution can be 0.25h to 4h, optionally 0.5h to 3h.

[0172] In some embodiments, when the modifying solution is an alkaline solution, the reaction can be performed at 100° C. to 145° C., and the reaction time of the cellulose powder and the modifying solution can be 0.5 h to 5 h.

[0173] In some embodiments, grinding can be performed using a grinder, and cutting can be performed using a high-pressure homogenizer. Nanocellulose with different average diameters and / or different average lengths can be obtained by adjusting the grinding parameters (e.g., grinding times, grinding time, etc.) of the grinder and the cutting parameters of the high-pressure homogenizer.

[0174] In some embodiments, the content of the first fiber material may be less than the content of the second fiber material.

[0175] By adjusting the content of the first fiber material to be less than that of the second fiber material, more second fiber materials can be better connected between the first fiber materials, which is beneficial for the first fiber material and the second fiber material to overlap to form a dendritic structure with more branches, thereby facilitating the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane, and further improving the battery cycle performance.

[0176] Optionally, the content of the first fiber material is recorded as W 11 , the content of the second fiber material is recorded as W 12 , are based on the total mass of the coating, W 11 / W 12 It can be 0.20-0.95, and can be optionally 0.40-0.75.

[0177] By further adjusting W 11 / W 12 Within the above range, the performance of the separator and the battery can be further improved.

[0178] In some embodiments, the content of the first fiber material is denoted as W 11 , based on the total mass of the coating, W 11 It may be 5wt%-13wt%.

[0179] In some embodiments, the content of the second fiber material is denoted as W 12 , based on the total mass of the coating, W 12 It may be 9wt%-21wt%.

[0180] By adjusting the content of the first fiber material and / or the second fiber material within the above range, the first fiber material and the second fiber material can be better overlapped, which is beneficial to increase the heat resistance of the isolation membrane, reduce the content of free filler particles in the coating, and facilitate the electrolyte to quickly wetting the isolation membrane along the first fiber material and the second fiber material, thereby improving the electrolyte wettability and liquid retention of the isolation membrane.

[0181] In some embodiments, the granular filler may include a first filler and a second filler, and the average particle size D1 of the first filler may be smaller than the average particle size D2 of the second filler.

[0182] The particle size of the first filler is relatively small, and the gaps between the particles after accumulation are usually relatively small, which is conducive to forming a capillary-like effect, thereby improving the electrolyte infiltration speed of the isolation membrane; however, the air permeability, electrolyte retention capacity and ion transmission capacity of the isolation membrane are not excellent enough, which easily leads to problems such as increased internal resistance of the battery and increased self-heating during battery use. By making the granular filler include both the first filler and the second filler, and making the average particle size D1 of the first filler smaller than the average particle size D2 of the second filler, a certain space can be formed around the second filler particles in the coating, thereby improving the air permeability of the isolation membrane, and also facilitating the preservation of the electrolyte after infiltration, thereby facilitating the improvement of the electrolyte retention and ion transmission properties of the isolation membrane.

[0183] The particle size of the second filler is relatively large, and the gaps between the particles after accumulation are usually relatively large. When the battery is abnormally heated, the second filler particles will contact with the porous substrate as it shrinks, resulting in insufficient heat resistance of the separator. By making the granular filler include both the first filler and the second filler, and making the average particle size D1 of the first filler smaller than the average particle size D2 of the second filler, the first filler particles can be filled in the gaps between the second filler particles, thereby reducing the thermal shrinkage of the separator and improving the heat resistance of the separator.

[0184] Optionally, the average particle size D1 of the first filler and the average particle size D2 of the second filler satisfy D2 / D1≥1.2.

[0185] Optionally, D2 / D1 may be 1.5-16, more preferably 2-8.

[0186] By further adjusting D2 / D1 within the above range, the performance of the isolation membrane can be better improved so that it has good air permeability, good electrolyte wettability and liquid retention as well as good heat resistance. The first filler and the second filler can also be better overlapped with the first fiber material and the second fiber material to form an integrated coating, thereby reducing the content of free filler particles, thereby further reducing the risk of failure during battery use and further improving the battery's cycle performance.

[0187] In some embodiments, the first filler has a secondary particle morphology and the second filler has a primary particle morphology.

[0188] The secondary particles are formed by agglomeration of multiple primary particles, and the first filler in the secondary particle morphology can better overlap with the first fiber material and the second fiber material to form an integrated coating, thereby helping to make the coating have a stable spatial network structure and helping to improve the heat resistance of the separator. The second filler in the primary particle morphology is conducive to reducing the moisture content of the coating, improving the air permeability and ion conductivity of the coating, and thus helping to improve the cycle performance of the battery.

[0189] In some embodiments, a ratio L1 / D2 of an average length L1 of the first fiber material to an average particle size D2 of the second filler may be 3.0-5.0.

[0190] The first fiber material is mainly used to connect the second filler with a larger particle size, and can also connect the first filler with a smaller particle size. By making L1 / D2 within the above range, the first fiber material in the coating can connect more second filler particles, which is conducive to forming an integrated coating, and further conducive to improving the heat resistance, electrolyte wettability and liquid retention of the separator.

[0191] In some embodiments, a ratio L2 / D1 of an average length L2 of the second fiber material to an average particle size D1 of the first filler may be 2.0-4.0.

[0192] The second fiber material is used to connect the first filler with a smaller particle size. By making L2 / D1 within the above range, the second fiber material in the coating can connect more second filler particles, which is conducive to forming an integrated coating, and further conducive to improving the heat resistance, electrolyte wettability and liquid retention of the separator.

[0193] In some embodiments, the average particle size D1 of the first filler may be less than 200 nm, and may be 50 nm-185 nm.

[0194] When the average particle size of the first filler is within the above range, it is easier to overlap with the first fiber material and the second fiber material to form an integrated coating, thereby improving the heat resistance, electrolyte wettability and liquid retention of the isolation membrane.

[0195] In some embodiments, the average particle size D2 of the second filler may be 200 nm-800 nm, and may be 210 nm-400 nm.

[0196] The average particle size of the second filler is within the above range, which is beneficial for maintaining a stable pore structure of the coating during long-term charge and discharge, reducing the moisture content of the coating, and improving the air permeability and ion conductivity of the coating, thereby improving the cycle performance of the battery.

[0197] The average particle size of the first filler and the second filler can be tested using equipment and methods known in the art. For example, a scanning electron microscope (such as ZEISS Sigma 300) can be used to map the microscopic morphology of the porous coating in the sample, and a scanning electron microscope (SEM) image of the porous coating of the isolation membrane can be obtained by referring to JY / T 0584-2020. The longest diagonal length of the particles is measured through the SEM image and then the average value is obtained. The number of selected particles can be more than 100.

[0198] In some embodiments, the average particle size of the primary particles constituting the first filler may be 10 nm to 50 nm, and may be 15 nm to 35 nm.

[0199] The average particle size of the primary particles constituting the first filler is within the above range, so that the first filler has a good secondary particle morphology, which is beneficial to improving the overlapping effect of the first filler with the first fiber material and the second fiber material.

[0200] In some embodiments, the specific surface area of ​​the first filler may be greater than the specific surface area of ​​the second filler.

[0201] The first filler has a larger specific surface area and better affinity with the first fiber material and the second fiber material, so that the coating can have a more stable spatial network structure and the isolation membrane has better heat resistance and higher ion conductivity; the second filler has a smaller specific surface area, which is beneficial to reducing the moisture content of the isolation membrane.

[0202] In some embodiments, the specific surface area of ​​the first filler may be greater than or equal to 20 m 2 / g, optional 30m 2 / g-80m 2 / g.

[0203] When the specific surface area of ​​the first filler is within the above range, it is beneficial to further improve the heat resistance and ion conductivity of the isolation membrane; in addition, it is also beneficial to improve the affinity of the first filler with the first fiber material and the second fiber material, so that the coating can have a more stable spatial network structure, and the isolation membrane has better heat resistance and higher ion conductivity.

[0204] In some embodiments, the specific surface area of ​​the second filler may be less than 20 m 2 / g, optional 5m 2 / g-15m 2 / g.

[0205] The specific surface area of ​​the second filler is within the above range, which is beneficial to reducing the moisture content of the isolation membrane, thereby reducing the battery capacity decay rate and improving the cycle performance of the battery.

[0206] The specific surface area of ​​the first filler and the second filler is a well-known meaning in the art, and can be measured using instruments and methods known in the art. For example, it can be tested by nitrogen adsorption specific surface area analysis test method with reference to GB / T 19587-2017, and calculated by BET (BrunauerEmmett Teller) method. Optionally, the nitrogen adsorption specific surface area analysis test can be performed by Tri-Star 3020 specific surface area pore size analysis tester of Micromeritics, USA.

[0207] In some embodiments, the content of the first filler may be greater than that of the second filler, thereby facilitating better performance of the first filler and the second filler, improving the heat resistance of the isolation membrane, and improving the electrolyte retention of the isolation membrane.

[0208] Optionally, the content of the first filler is recorded as W 21 , the content of the second filler is recorded as W 22 , are based on the total mass of the coating, W 22 / W 21 It can be 0.10-0.80, and can be optionally 0.25-0.50.

[0209] In some embodiments, the content of the first filler is denoted as W 21 , based on the total mass of the coating, W 21 It may be 20wt%-70wt%, optionally 36wt%-61.5wt%.

[0210] The content of the first filler within the above range is conducive to the coating slurry having a suitable viscosity, which is more conducive to coating; in addition, it is also conducive to the coating having a more stable spatial network structure, thereby making the isolation membrane have better heat resistance and higher ion conductivity.

[0211] In some embodiments, the content of the second filler is denoted as W 22 , are based on the total mass of the coating, W 22 It may be 5wt%-60wt%, optionally 10wt%-35wt%.

[0212] The content of the second filler within the above range is beneficial for the coating to maintain a stable pore structure during long-term charge and discharge, thereby reducing the moisture content of the isolation membrane and preserving the electrolyte after infiltration, thereby improving the cycle performance of the battery.

[0213] In some embodiments, the total content W1 of the fiber material may be 14 wt%-35 wt%, optionally 15 wt%-30 wt%, based on the total weight of the coating. 11 +W 12 .

[0214] In some embodiments, the total content W2 of the particulate filler may be greater than or equal to 60 wt%, and may be 68 wt%-83 wt%, based on the total mass of the coating. 21 +W 22 .

[0215] By adjusting the total content of the fiber material and the total content of the granular filler within the above range, the coating slurry can have a suitable viscosity, which is more conducive to coating; in addition, it is also beneficial for the first fiber material, the second fiber material to overlap with the first filler and the second filler to form an integrated coating, thereby enabling the coating to have a more stable spatial network structure, thereby further improving the heat resistance, air permeability, electrolyte wettability and liquid retention of the isolation membrane.

[0216] In some embodiments, the first filler may include at least one of inorganic particles and organic particles.

[0217] Optionally, the inorganic particles may include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silica, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate and magnesium fluoride, more optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, silica, titanium oxide, zinc oxide, cerium oxide and barium titanate.

[0218] Alternatively, the organic particles may include at least one of polystyrene and polyacrylic wax.

[0219] In some embodiments, the first filler includes inorganic particles with secondary particle morphology, and the crystal form of the inorganic particles with secondary particle morphology may include at least two of α-crystal form, θ-crystal form, γ-crystal form and η-crystal form. Optionally, the crystal form of the inorganic particles with secondary particle morphology may include at least two of α-crystal form, θ-crystal form and γ-crystal form.

[0220] Optionally, the content of inorganic particles with α-crystal secondary particle morphology in the inorganic particles with secondary particle morphology may be greater than or equal to 1.2 wt%, more optionally 1.2 wt% to 10 wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0221] Optionally, the content of inorganic particles with secondary particle morphology of θ crystal type in inorganic particles with secondary particle morphology can be greater than or equal to 50wt%, more optionally 60wt% to 85wt%, based on the total mass of inorganic particles with secondary particle morphology.

[0222] Optionally, the content of inorganic particles with secondary particle morphology of γ crystal type in the inorganic particles with secondary particle morphology can be greater than or equal to 10wt%, and more optionally 15wt% to 60wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0223] Optionally, the content of inorganic particles with secondary particle morphology of η crystal type in the inorganic particles with secondary particle morphology can be less than or equal to 5wt%, and more optionally less than or equal to 2wt%, based on the total mass of the inorganic particles with secondary particle morphology.

[0224] The inorganic particles of the θ crystal form have a moderate specific surface area and hardness, thereby being able to better improve the heat resistance and ion conductivity of the isolation membrane at the same time; the inorganic particles of the γ crystal form and the η crystal form have the advantage of a large specific surface area. Selecting first fillers of different crystal forms helps to improve at least one of the heat resistance, ion conductivity, bonding strength, electrolyte wettability and liquid retention of the isolation membrane.

[0225] In some embodiments, inorganic particles with secondary particle morphology can be prepared as follows: a precursor solution of the inorganic particles is subjected to an oxidation reaction by high-pressure sputtering, and then heated at 600°C to 1200°C (e.g., 1 hour to 3 hours) to form inorganic particles with primary particle morphology, and then dried and formed at 150°C to 250°C (e.g., 30 minutes to 60 minutes) to obtain inorganic particles with secondary particle morphology (obtained by primary particle assembly).

[0226] In some embodiments, the second filler may include at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reactions.

[0227] Alternatively, inorganic particles having a dielectric constant of 5 or more may include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3 )O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. Chemical modification methods include coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. Physical modification methods may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling the coating to have a more stable and uniform spatial network structure; in addition, by selecting a coupling agent, surfactant or polymer with a specific functional group to modify the inorganic particles, it is also helpful to improve the electrolyte wettability and liquid retention of the coating and improve the adhesion of the coating to the porous substrate.

[0228] Alternatively, inorganic particles having ion conductivity but not storing ions may include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, Lithium Aluminum Titanate Phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, Lithium Germanium Phosphate Thiophosphate x5 Ge y5 P z2 S w 、Lithium Nitride Li x6 N y6 、SiS2 glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion conductivity of the isolation membrane.

[0229] Alternatively, the inorganic particles capable of electrochemical reaction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates, carbon-based materials, silicon-based materials, tin-based materials, and lithium-titanium compounds.

[0230] In some embodiments, the second filler may include inorganic particles in a primary particle morphology, and the crystal form of the inorganic particles in the primary particle morphology may include at least one of an α crystal form and a γ crystal form, and may optionally include an α crystal form.

[0231] Optionally, the content of the inorganic particles with α-crystal primary particle morphology in the inorganic particles with primary particle morphology may be greater than or equal to 90 wt %, more optionally 95 wt % to 100 wt %, based on the total mass of the inorganic particles with primary particle morphology.

[0232] The α-crystal inorganic particles have the advantages of high hardness, good heat resistance, low dielectric constant, high safety and high true density, thereby further improving the heat resistance of the coating.

[0233] The inorganic particles of the θ crystal form have diffraction peaks at 36.68°±0.2° and 31.21°±0.2° in the X-ray diffraction spectrum measured by using an X-ray diffractometer. The inorganic particles of the γ crystal form have diffraction peaks at 66.95°±0.2° and 45.91°±0.2° in the X-ray diffraction spectrum measured by using an X-ray diffractometer. The inorganic particles of the η crystal form have diffraction peaks at 31.89°±0.2° and 19.37°±0.2° in the X-ray diffraction spectrum measured by using an X-ray diffractometer. The inorganic particles of the α crystal form have diffraction peaks at 57.48°±0.2° and 43.34°±0.2° in the X-ray diffraction spectrum measured by using an X-ray diffractometer.

[0234] The X-ray diffraction spectrum of inorganic particles can be obtained by testing as follows: After drying the inorganic particles, grind them in a mortar (such as an agate mortar) for 30 minutes, and then use an X-ray diffractometer (such as Miniflex600-C) to test and obtain the X-ray diffraction spectrum. The test can use a Cu target, a Ni filter, a tube voltage of 40KV, a tube current of 15mA, and a continuous scanning range of 5°-80°.

[0235] In some embodiments, the coating may also include a non-granular binder. The present application has no particular restrictions on the type of non-granular binder, and any known material with good adhesion may be selected. Alternatively, the non-granular binder may include an aqueous solution binder, which has the advantages of good thermodynamic stability and environmental protection, thereby facilitating the preparation and application of the coating slurry. As an example, the aqueous solution binder may include at least one of an aqueous solution type acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, sodium acrylate monomers or a copolymer with other comonomers), polyvinyl alcohol (PVA), an isobutylene-maleic anhydride copolymer, and polyacrylamide.

[0236] Optionally, the content of the non-granular binder in the coating can be less than or equal to 2wt%, based on the total mass of the coating. The fiber material and the granular filler in the coating can form a stable spatial network structure, thereby enabling the isolation film to maintain high adhesion while reducing the amount of binder.

[0237] In some embodiments, the thickness of the coating may be less than or equal to 3 μm, and may be 0.3 μm-2 μm, and may be 0.5 μm-1.2 μm. This is beneficial to improving the energy density of the battery. The thickness of the coating refers to the thickness of the coating on one side of the porous substrate.

[0238] The embodiments of the present application have no particular restrictions on the material of the porous substrate, and any known substrate with good chemical stability and mechanical stability can be selected. For example, the porous substrate can include at least one of a porous polyolefin-based resin film (e.g., polyethylene, polypropylene, polyvinylidene fluoride), a porous aramid film, a porous polyimide film, a porous glass fiber, and a porous non-woven fabric. The porous substrate can be a single-layer film or a multi-layer composite film. When the porous substrate is a multi-layer composite film, the materials of each layer can be the same or different.

[0239] In some embodiments, the thickness of the porous substrate may be less than or equal to 5 μm, and may be 3 μm-4.5 μm.

[0240] In some embodiments, the separator may further include an adhesive layer, which is disposed on at least a portion of the surface of the coating. The adhesive layer can not only prevent the coating from falling off and improve the reliability of the battery, but also improve the interface between the separator and the electrode (e.g., the positive electrode and the negative electrode), thereby facilitating the improvement of the cycle performance of the battery.

[0241] In some embodiments, the adhesive layer may include a particulate adhesive. Optionally, the particulate adhesive may include at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.

[0242] The comonomer may include, but is not limited to, at least one of the following: an acrylate monomer, an acrylic acid monomer, an olefin monomer, a halogen-containing olefin monomer, a fluoroether monomer, and the like.

[0243] Alternatively, the granular binder may include a vinylidene fluoride based polymer, such as a homopolymer of vinylidene fluoride monomer (VDF) and / or a copolymer of vinylidene fluoride monomer and a comonomer. The comonomer may be at least one of an olefin monomer, a fluorine-containing olefin monomer, a chlorine-containing olefin monomer, an acrylate monomer, an acrylic monomer, and a fluoroether monomer. Alternatively, the comonomer may include at least one of trifluoroethylene (VF3), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro (alkyl vinyl) ether (e.g., perfluoro (methyl vinyl) ether PMVE, perfluoro (ethyl vinyl) ether PEVE, perfluoro (propyl vinyl) ether PPVE), perfluoro (1,3-dioxole) and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).

[0244] In some embodiments, the heat shrinkage of the isolation film in the transverse direction and the longitudinal direction at 150° C. for 1 hour may be less than 2%.

[0245] The separator has a low thermal shrinkage rate at high temperatures, thereby being able to improve the reliability of the battery.

[0246] In some embodiments, the air permeability of the isolation membrane may be less than or equal to 300 s / 100 mL, and may be 100 s / 100 mL-240 s / 100 mL.

[0247] The separator has good air permeability, thereby improving the ion conductivity of the separator and the battery capacity performance characteristics.

[0248] In some embodiments, the wetting speed of the isolation film may be greater than or equal to 3 mm / s, and may be 5 mm / s-15 mm / s.

[0249] The separator has good electrolyte wettability, thereby improving the ion conductivity of the separator and the battery capacity performance characteristics.

[0250] The heat shrinkage and air permeability of the isolation film have well-known meanings in the art and can be measured using methods known in the art. For example, both can be tested with reference to GB / T 36363-2018.

[0251] The wetting speed of the isolation membrane has a well-known meaning in the art and can be measured by methods known in the art. An exemplary test method is as follows: cut the isolation membrane into samples with a width of 5 mm and a length of 100 mm, fix the two ends of the sample and place it horizontally; take 0.5 mg of electrolyte and drop it in the center of the sample. After reaching the specified time (1 min in this application), take a picture and measure the length of the electrolyte diffusion, thereby obtaining the wetting speed of the isolation membrane. In order to ensure the accuracy of the test results, multiple (for example, 5 to 10) samples can be taken for testing, and the test results are obtained by calculating the average value. The electrolyte can be prepared as follows: ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and the fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0252] It should be noted that the coating parameters (such as thickness, etc.) of the above-mentioned isolation membrane are the coating parameters of one side of the porous substrate. When the coating is provided on both sides of the porous substrate, the coating parameters of either side satisfy the present application and are considered to fall within the protection scope of the present application.

[0253] [Preparation method]

[0254] The present application also provides a method for preparing the above-mentioned isolation film.

[0255] The method comprises the following steps: providing a porous substrate; mixing a first fiber material, a second fiber material, and a granular filler in a solvent in a predetermined ratio to prepare a coating slurry; coating the coating slurry on at least one surface of the porous substrate, and obtaining an isolation membrane after drying.

[0256] In some embodiments, the solvent used in preparing the coating slurry may be water, such as deionized water.

[0257] In some embodiments, the coating slurry may further include other components, for example, a dispersant, a wetting agent, a binder, a surfactant, etc.

[0258] In some embodiments, a coating slurry may be applied using a coating machine. The present application has no particular restrictions on the type of coating machine, for example, a commercially available coating machine may be used. The coating machine may include a gravure roller; the gravure roller is used to transfer the slurry to the porous substrate.

[0259] In some embodiments, the preparation method may further include the following steps: applying a slurry containing a granular binder on at least a portion of the surface of the coating layer, and forming an adhesive layer after drying.

[0260] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane can refer to the above-mentioned isolation membrane and will not be repeated here.

[0261] Unless otherwise specified, all raw materials used in the method for preparing the isolation membrane can be obtained commercially.

[0262] [Positive electrode]

[0263] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and including a positive electrode active material. For example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0264] When the battery is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of lithium transition metal oxides, lithium-containing phosphates, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.

[0265] In some embodiments, in order to further improve the energy density of the battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of lithium transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes but is not limited to at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes but is not limited to at least one of N, F, S and Cl.

[0266] As an example, the positive electrode active material for lithium ion batteries may include, but is not limited to, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.8 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.

[0267] When the battery is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.

[0268] As an example, the positive electrode active material for sodium ion batteries may include, but is not limited to, NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x In the general formula X p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes but is not limited to H + , Li + 、Na + , K + and NH4 + At least one of, M' is a transition metal cation, optionally including but not limited to at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.

[0269] The modified compounds of the above-mentioned positive electrode active materials may be the ones that undergo doping modification and / or surface coating modification on the positive electrode active materials.

[0270] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include but is not limited to at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0271] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.

[0272] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material may include but is not limited to at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0273] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, the optional positive electrode conductive agent, the optional positive electrode binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0274] [Negative electrode]

[0275] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0276] The negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include, but is not limited to, at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy material. The tin-based material may include, but is not limited to, at least one of elemental tin, tin oxide, and tin alloy material.

[0277] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include but is not limited to at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0278] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the negative electrode binder may include, butadiene styrene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS) at least one.

[0279] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0280] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include but is not limited to at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include but is not limited to at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0281] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, the optional negative electrode conductive agent, the optional negative electrode binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0282] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0283] [Electrolyte]

[0284] The electrolyte conducts ions between the positive electrode and the negative electrode.

[0285] In some embodiments, the electrolyte may include an electrolyte salt and a solvent.

[0286] When the battery is a lithium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0287] When the battery is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).

[0288] In some embodiments, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).

[0289] In some embodiments, the electrolyte may further include an additive. As an example, the additive may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), and vinylene carbonate (VC).

[0290] Optionally, the total mass of the additives may be 0.5 wt%-12 wt% of the total mass of the electrolyte, and may be optionally 2 wt%-8 wt%.

[0291] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After vacuum packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0292] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0293] The electric device can select the type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.

[0294] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module may be used.

[0295] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0296] Example

[0297] The following examples describe the disclosure of the present application in more detail, and these examples are only for illustrative purposes, as it is obvious to those skilled in the art that various modifications and variations can be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.

[0298] The nanocellulose used in the present application can be purchased from the market or prepared by the following method.

[0299] Preparation of Nanocellulose

[0300] The cotton linters were opened and deslagging by a cotton opener, and then boiled at 150°C for 2 hours using a 5wt% NaOH aqueous solution. The cotton linters were then washed with water to remove impurities (the number of washings was 3 times), bleached with sodium hypochlorite, washed with dilute hydrochloric acid to remove impurities, washed with water to remove impurities (the number of washings was 1 time), driven out of water, and dried with air flow to obtain cotton cellulose powder with a whiteness greater than or equal to 85%.

[0301] 1 kg of the obtained cotton cellulose powder was mixed with 30 kg of a 60 wt % aqueous sulfuric acid solution, and reacted at 55° C. to 60° C. for 0.5 h to 1.5 h. After the reaction, the mixture was washed with water to remove impurities (washed 3 times), filtered, and deacidified and impurified. The pH was adjusted to neutral with a 10 wt % aqueous NaOH solution, and then ground with a grinder. Nano-scale cutting was performed using a high-pressure homogenizer to obtain nanocellulose having sulfonic acid modified groups, and the molar ratio of sulfonic acid groups to surface hydroxyl groups was between 3:3 and 5:3.

[0302] During the preparation process, nanocelluloses with different average diameters and / or different average lengths can be obtained as the first nanocellulose and the second nanocellulose, respectively, by adjusting the reaction concentration, reaction time, grinding machine processing parameters, and cutting parameters of the high-pressure homogenizer equipment.

[0303] Example 1

[0304] Preparation of positive electrode

[0305] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent acetylene black, and binder polyvinylidene fluoride are mixed in a mass ratio of 94:3:3, and an appropriate amount of solvent NMP is added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry is coated on both surfaces of the positive electrode current collector aluminum foil, and after drying, cold pressing, and slitting, a positive electrode sheet is obtained.

[0306] Preparation of negative electrode

[0307] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and after drying, cold pressing and slitting, a negative electrode sheet is obtained.

[0308] Preparation of isolation membrane

[0309] Provide PE porous substrate: thickness is 4.5μm.

[0310] Preparation of coating slurry: uniformly mix the first fiber material, the second fiber material, the first filler, the second filler, and the binder polyacrylic acid in a mass ratio of 10:18:52:18:2 in an appropriate amount of solvent deionized water to obtain a coating slurry.

[0311] The first fiber material is first nanocellulose with an average length of 1500 nm, an average diameter of 50 nm, and an aspect ratio of 30.

[0312] The second fiber material is second nanocellulose with an average length of 350 nm, an average diameter of 20 nm, and an aspect ratio of 17.5.

[0313] The first filler is alumina with secondary particle morphology, and the volume distribution particle size Dv50 is 140nm. The contents of α crystal, θ crystal, γ crystal and η crystal in the alumina are 1.1wt%, 68.7wt%, 29.6wt% and 0.6wt%, respectively, based on the total mass of the alumina.

[0314] The second filler is alumina in primary particle morphology, with a volume distribution particle size Dv50 of 320 nm, and the crystal form of the alumina is mainly α crystal form, with a content of more than 99 wt % based on the total mass of the alumina.

[0315] Coating: The prepared coating slurry is coated on both surfaces of the PE porous substrate by micro-gravure, and the isolation film is obtained through drying and slitting processes. The coating thickness on one side of the PE porous substrate is 0.75 μm.

[0316] Preparation of electrolyte

[0317] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 20:80 to obtain an organic solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L. Then, fluoroethylene carbonate (FEC) and 1,3-propane sultone (PS) are added, and the mass content of FEC is 3wt% of the total mass of the electrolyte, and the mass content of PS is 0.5wt% of the total mass of the electrolyte.

[0318] Preparation of batteries

[0319] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer packaging aluminum shell, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a battery is obtained.

[0320] Example 2

[0321] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the average length of the second fiber material was 250 nm, the average diameter was 20 nm, and the aspect ratio was 12.5.

[0322] Example 3

[0323] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the average length of the second fiber material was 550 nm, the average diameter was 20 nm, and the aspect ratio was 27.5.

[0324] Example 4

[0325] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the first fiber material had an average length of 850 nm, an average diameter of 50 nm, and an aspect ratio of 17.

[0326] Example 5

[0327] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the first fiber material had an average length of 1050 nm, an average diameter of 50 nm, and an aspect ratio of 21.

[0328] Example 6

[0329] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the average length of the first fiber material was 2000 nm, the average diameter was 50 nm, and the aspect ratio was 40.

[0330] Example 7

[0331] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the first fiber material had an average length of 3000 nm, an average diameter of 50 nm, and an aspect ratio of 60.

[0332] Example 8

[0333] The battery was prepared by a method similar to that of Example 1, except that in the preparation of the isolation membrane, the mass ratio of the first fiber material, the second fiber material, the first filler, the second filler, and the binder polyacrylic acid was 15:13:52:18:2.

[0334] Comparative Example 1

[0335] The battery was prepared by a method similar to that of Example 1, except that when preparing the isolation membrane, the second fiber material was not added to the coating slurry, and the mass ratio of the first fiber material, the first filler, the second filler, and the binder polyacrylic acid was 28:52:18:2.

[0336] Performance Testing

[0337] (1) Hot box performance test of battery

[0338] At 25°C, charge the battery to 4.2V at 1C constant current, continue to charge at constant voltage until the current is less than or equal to 0.05C, and let it stand for 5 minutes; then test each battery with a fixture in the DHG-9070ADHG series high temperature oven, increase the temperature from 25°C to 60°C±2°C at a rate of 5°C / min, and keep it for 30 minutes; then increase the temperature at a rate of 5°C / min, and keep it warm for 30 minutes every time the temperature rises by 5°C, and record the hot box temperature and insulation time when the battery fails. The higher the hot box failure temperature of the battery, the better the thermal stability of the battery. When the hot box failure temperature of the battery is the same, the longer the insulation time, the better the thermal stability of the battery. For accuracy, take the average value of 5 parallel samples as the test result.

[0339] (2) Battery cycle performance test

[0340] At 25°C, charge the battery to 4.2V at a constant current of 0.33C, and continue to charge at a constant voltage until the current is less than or equal to 0.05C. At this time, the battery is fully charged. Record the charging capacity at this time, which is the charging capacity of the first cycle; after the battery is left to stand for 5 minutes, discharge it to 2.8V at a constant current of 1C. This is a cyclic charge and discharge process. Record the discharge capacity at this time, which is the discharge capacity of the first cycle. Perform a cyclic charge and discharge test on the battery according to the above method, and record the discharge capacity after each cycle. The capacity retention rate (%) of the battery after 1000 cycles at 25°C = discharge capacity after 1000 cycles / discharge capacity of the first cycle × 100%. For accuracy, take the average value of 5 parallel samples as the test result.

[0341] The test results of Examples 1 to 8 and Comparative Example 1 are shown in Table 1.

[0342] It can be seen from the test results in Table 1 that by making the fiber material in the isolation membrane coating include both the first fiber material and the second fiber material, and making the average length L1 of the first fiber material and the average length L2 of the second fiber material satisfy L1 greater than 800 nm and L1 / L2 ≥ 2.4, the battery can have high thermal stability and good cycle performance.

[0343] It can also be seen from the test results of Examples 1 to 7 that by further adjusting one or more of the average length L1 of the first fiber material, the average length L2 of the second fiber material, the average particle size D1 of the first filler, the average particle size D2 of the second filler, L1 / L2, L1 / D2, and L2 / D1, the thermal stability and cycle performance of the battery can be further improved.

[0344] It can also be seen from the test results of Example 1 and Example 8 that the cycle performance of the battery can be further improved by making the content of the first fiber material in the isolation film coating less than the content of the second fiber material.

[0345] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

[0346]

Claims

1. A separator, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate, characterized in that: The coating includes a fiber material and a granular filler, the fiber material includes a first fiber material and a second fiber material, the average length of the first fiber material is denoted as L1, the average length of the second fiber material is denoted as L2, L1 is greater than 800 nm, and L1 / L2≥2.

4.

2. The isolation film according to claim 1, characterized in that: L1 / L2 is 2.4-9.0, and can be optionally 2.7-5.

8.

3. The isolation film according to any one of claims 1 to 2, characterized in that: The average length L1 of the first fiber material is 850nm-3000nm, and can be 1000nm-2000nm; and / or, The average length L2 of the second fiber material is 200nm-800nm, and can be optionally 300nm-550nm.

4. The isolation membrane according to any one of claims 1 to 3, characterized in that: The average diameter of the first fiber material is greater than the average diameter of the second fiber material; Optionally, the average diameter of the first fiber material is less than or equal to 100 nm, and more preferably 25 nm to 75 nm; Optionally, the average diameter of the second fiber material is 12 nm-40 nm, more preferably 15 nm-32 nm.

5. The isolation film according to any one of claims 1 to 4, characterized in that: The aspect ratio of the first fiber material is greater than the aspect ratio of the second fiber material; Optionally, the aspect ratio of the first fiber material is 12-100, more preferably 20-50; Optionally, the aspect ratio of the second fiber material is 10-70, more preferably 15-40.

6. The isolation film according to any one of claims 1 to 5, characterized in that: The content of the first fiber material is less than the content of the second fiber material; Optionally, the content of the first fiber material is recorded as W 11 , the content of the second fiber material is recorded as W 12 , are based on the total mass of the coating, W 11 / W 12 0.20-0.95, and more preferably 0.40-0.75; Optionally, the content of the first fiber material is recorded as W 11 , based on the total mass of the coating, W 11 5wt%-13wt%; Optionally, the content of the second fiber material is recorded as W 12 , based on the total mass of the coating, W 12 9wt%-21wt%.

7. The isolation membrane according to any one of claims 1 to 6, characterized in that: The first fiber material and the second fiber material each independently include at least one of an organic fiber material and an inorganic fiber material; Optionally, the organic fiber material includes at least one of nanocellulose, polytetrafluoroethylene nanofibers and polyamide nanofibers; Optionally, the inorganic fiber material includes at least one of halloysite nanotubes, nanorod-shaped aluminum oxide, nanorod-shaped boehmite, nanorod-shaped silicon oxide and glass fiber.

8. The isolation membrane according to any one of claims 1 to 7, characterized in that: The first fiber material and the second fiber material each independently comprise nanocellulose; Optionally, the nanocellulose includes a modified group, and the modified group includes at least one of an amine group, a carboxyl group, an aldehyde group, a sulfonic acid group, and a phosphoric acid group, and more optionally includes at least one of a sulfonic acid group and a phosphoric acid group; Optionally, the nanocellulose includes hydroxyl groups and modified groups, and the molar ratio of the modified groups to the hydroxyl groups is 1:4 to 4:1, and more preferably 2:3 to 7:

3.

9. The isolation film according to any one of claims 1 to 8, characterized in that: The granular filler includes a first filler and a second filler, wherein the average particle size D1 of the first filler is smaller than the average particle size D2 of the second filler; The average particle size D1 of the first filler and the average particle size D2 of the second filler satisfy D2 / D1≥1.2; optionally, D2 / D1 is 1.5-16, and more optionally 2-8.

10. The isolation film according to claim 9, characterized in that: The first filler has a secondary particle morphology, and the second filler has a primary particle morphology.

11. The isolation film according to any one of claims 9 to 10, characterized in that: The ratio L1 / D2 of the average length L1 of the first fiber material to the average particle size D2 of the second filler is 3.0-5.0; and / or, The ratio L2 / D1 of the average length L2 of the second fiber material to the average particle size D1 of the first filler is 2.0-4.

0.

12. The isolation membrane according to any one of claims 9 to 11, characterized in that: The average particle size D1 of the first filler is less than 200 nm, and may be 50 nm-185 nm; and / or, The average particle size D2 of the second filler is 200nm-800nm, and can be optionally 210nm-400nm.

13. The isolation membrane according to any one of claims 9 to 12, characterized in that: The average particle size of the primary particles constituting the first filler is 10 nm-50 nm, and can be optionally 15 nm-35 nm.

14. The isolation membrane according to any one of claims 9 to 13, characterized in that: The specific surface area of ​​the first filler is greater than the specific surface area of ​​the second filler; Optionally, the specific surface area of ​​the first filler is greater than or equal to 20m 2 / g, 30m is optional 2 / g-80m 2 / g; Optionally, the specific surface area of ​​the second filler is less than 20m 2 / g, 5m is optional 2 / g-15m 2 / g.

15. The isolation film according to any one of claims 9 to 14, characterized in that: The content of the first filler is greater than the content of the second filler; Optionally, the content of the first filler is recorded as W 21 , the content of the second filler is recorded as W 22 , are based on the total mass of the coating, W 22 / W 21 0.10-0.80, and more preferably 0.25-0.50; Optionally, the content of the first filler is recorded as W 21 , based on the total mass of the coating, W 21 20wt%-70wt%, more preferably 36wt%-61.5wt%; Optionally, the content of the second filler is recorded as W 22 , based on the total mass of the coating, W 22 It is 5wt%-60wt%, and more preferably 10wt%-35wt%.

16. The isolation membrane according to any one of claims 9 to 15, characterized in that: The first filler includes at least one of inorganic particles and organic particles; optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate and magnesium fluoride, more optionally, the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, silicon oxide, titanium oxide, zinc oxide, cerium oxide and barium titanate; optionally, the organic particles include at least one of polystyrene and polyacrylic wax; and / or, The second filler includes at least one of inorganic particles having a dielectric constant of 5 or more, inorganic particles having ion conductivity but not storing ions, and inorganic particles capable of electrochemical reaction.

17. The isolation membrane according to any one of claims 9 to 16, characterized in that: The first filler comprises inorganic particles in a secondary particle morphology, and the crystal form of the inorganic particles in the secondary particle morphology comprises at least two of α crystal form, θ crystal form, γ crystal form and η crystal form. Optionally, the crystal form of the inorganic particles in the secondary particle morphology comprises at least two of α crystal form, θ crystal form and γ crystal form; Optionally, the content of the inorganic particles with secondary particle morphology of α crystal form in the inorganic particles with secondary particle morphology is greater than or equal to 1.2wt%, and more preferably 1.2wt% to 10wt%, based on the total mass of the inorganic particles with secondary particle morphology; Optionally, the content of the inorganic particles of the secondary particle morphology of the θ crystal form in the inorganic particles of the secondary particle morphology is greater than or equal to 50wt%, and more optionally 60wt% to 85wt%, based on the total mass of the inorganic particles of the secondary particle morphology; Optionally, the content of the inorganic particles with secondary particle morphology of γ crystal form in the inorganic particles with secondary particle morphology is greater than or equal to 10wt%, and more preferably 15wt% to 60wt%, based on the total mass of the inorganic particles with secondary particle morphology; Optionally, the content of inorganic particles with η crystal secondary particle morphology in the inorganic particles with secondary particle morphology is less than or equal to 5wt%, and more optionally less than or equal to 2wt%, based on the total mass of the inorganic particles with secondary particle morphology.

18. The isolation membrane according to any one of claims 9 to 17, characterized in that: The second filler comprises inorganic particles in a primary particle morphology, and the crystal form of the inorganic particles in the primary particle morphology comprises at least one of an α crystal form and a γ crystal form, and optionally comprises an α crystal form; Optionally, the content of inorganic particles with α-crystal primary particle morphology in the second filler is greater than or equal to 90 wt %, and more optionally 95 wt % to 100 wt %, based on the total mass of the second filler.

19. The isolation membrane according to any one of claims 1 to 18, characterized in that: The coating also includes a non-particulate binder; Optionally, the non-granular binder comprises an aqueous solution binder; Optionally, the content of the non-granular binder in the coating is less than or equal to 2 wt %, based on the total mass of the coating.

20. The isolation membrane according to any one of claims 1 to 19, characterized in that: The isolation film further comprises an adhesive layer, which is disposed on at least a portion of the surface of the coating. Optionally, the bonding layer comprises a granular binder; More optionally, the granular binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer.

21. The isolation film according to any one of claims 1 to 20, characterized in that: The isolation film satisfies at least one of the following conditions (1) to (5): (1) The thickness of the porous substrate is less than or equal to 5 μm, and can be 3 μm-4.5 μm; (2) The thickness of the coating is less than or equal to 3 μm, and can be selected to be 0.3 μm-2 μm; (3) The heat shrinkage of the isolation film in both the transverse and longitudinal directions at 150° C. for 1 hour is less than 2%; (4) The air permeability of the isolation membrane is less than or equal to 300s / 100mL, and can be 100s / 100mL-240s / 100mL; (5) The wetting speed of the isolation film is greater than or equal to 3 mm / s, and can be optionally 5 mm / s-15 mm / s.

22. A battery, characterized in that: The isolation film comprises the isolation film according to any one of claims 1 to 21.

23. An electrical device, characterized in that: Comprising the battery of claim 22.

Citation Information

Patent Citations

  • Separator, method of preparing the same, and lithium battery including the same

    CN110233223A

  • Coating material for light-weight lithium ion battery diaphragm, preparation method of coating material and light-weight lithium ion battery composite diaphragm

    CN113013549A

  • Non-woven fabric and battery diaphragm

    CN113725556A

  • Lithium ion battery diaphragm supporting layer and lithium ion battery diaphragm

    CN113725557A

  • Isolating membrane, preparation method thereof, and related secondary battery and electric device

    CN116964850A

Cited By

  • Separator, battery and electric device

    EP4815166A1

  • Separator, battery and electric device

    WO2025112327A1